2022
DOI: 10.3390/ijms23115977
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Retinoic Acid Signaling in the Pathogenesis of Pseudoexfoliation Syndrome

Abstract: Pseudoexfoliation (PEX) syndrome, a stress-induced fibrotic matrix process, is the most common recognizable cause of open-angle glaucoma worldwide. The recent identification of PEX-associated gene variants uncovered the vitamin A metabolic pathway as a factor influencing the risk of disease. In this study, we analyzed the role of the retinoic acid (RA) signaling pathway in the PEX-associated matrix metabolism and evaluated its targeting as a potential candidate for an anti-fibrotic intervention. We provided ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
1
6
2
Order By: Relevance
“…Retinoic acid signalling has been reported to play a role in XFG and XFS [ 12 ] but our enrichment analysis did not reveal any enrichment terms directly associated with retinoic acid signalling, metabolism or transport; although some genes that are important in retinoic acid pathways (such as STRA6) did appear in other enrichment terms such as “eye development” and “artery development”. To investigate retinoic acid pathways in our dataset, a custom gene list was created by combining gene lists of Reactome pathways R-HSA-5362517 Signaling by Retinoic Acid and GO:0001523 retinoid metabolic process resulting in a list of 118 unique genes in total.…”
Section: Resultscontrasting
confidence: 70%
See 3 more Smart Citations
“…Retinoic acid signalling has been reported to play a role in XFG and XFS [ 12 ] but our enrichment analysis did not reveal any enrichment terms directly associated with retinoic acid signalling, metabolism or transport; although some genes that are important in retinoic acid pathways (such as STRA6) did appear in other enrichment terms such as “eye development” and “artery development”. To investigate retinoic acid pathways in our dataset, a custom gene list was created by combining gene lists of Reactome pathways R-HSA-5362517 Signaling by Retinoic Acid and GO:0001523 retinoid metabolic process resulting in a list of 118 unique genes in total.…”
Section: Resultscontrasting
confidence: 70%
“…Retinoic acid signalling has been reported to play a role in the pathogenesis of XFG and to modulate the activated TGF-β pathway by changing levels of phosphorylation [ 12 ]. Our results showed differential expression of several genes involved in retinoic acid transport and signalling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Nishikiori et al reported an interesting result in terms of the relationship between RA and BRB. That is, RAR alpha caused significant reductions in vascular leakage in the diabetic retina by antagonizing the loss of tight junction integrity that is induced by diabetes [ 38 ]. These observations corresponded well with our current results, which show that ATRA exerts synergistic and beneficial effects in TGF-β2-treated 2D- and 3D-cultured HTM cells; our results were found through in vitro models that replicate the single- and multiple-sheet barrier structures of the HTM [ 25 , 26 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%